Pembinaan Kelompok Tani Sintuvu Roso Dalam Pengelolaan Hutan Kemasyarakatan - Hamka Hamka; Arman Maiwa; Abdul Hapid; Muthmainnah Muthmainnah; Hendra Pribadi (Politeknik Negeri Cilacap, 2023)
Community forestry (HKm) is a state forest that aims to empower communities around the forest without disturbing its main function, whose management is carried out by farmer groups. However, there are still many members of farmer groups who do not understand HKm management. This service activity is carried out to increase the knowledge of farmer groups as community forest managers. The target of this activity is the Sintuvu Roso farmer group, Wombo Kalonggo Village, Tanantovea District, Donggala Regency. Based on the results of observations, situation analysis and problem identification, it was discovered that the partners had problems, including the social forestry work plan and annual work plan had not been prepared, and many group members did not know the HKm limits. The stages of the implementation of community service consist of observation, problem identification, counseling and training, evaluation of activities and preparation of reports. The solution to this problem is that partners carry out counseling activities on how to manage and prepare HKm work plans and training on using Avenza maps. The results of the implementation of the service that has been carried out are increasing the knowledge of farmer groups in managing community forests and using the Avenza Maps application.